Education in the Context of Internationalization, Immigration, and Forced Migration: Introduction to the Special Issue - White, Melissa; Domene, Jose (Antistasis, 2017)
We introduce this special issue of Antistasis on internationalization, immigration and forced migration. The 21st century has witnessed an increase in the movement of individuals and families across national boundaries for a multitude of reasons, including voluntary immigration, forced migration, and temporary relocation for education or employment. These trends require the education system in Canada and internationally to adapt to the changing nature of students (and teachers and support staff) from early childhood to post-secondary, which in turn requires thoughtful reflection and discussion by education researchers and scholar-practitioners working within the education system.